Исламская религия в контексте демократизации современного азербайджанского общества - Гасанов, Н.А. (Мультиверсум. Філософський альманах, 2009)
Islam religion within the context of democratized society of modern Azerbaijan
In all the human story the existance of the religion is accepted by all regardless the social
systems. The general and universal character of the religion makes a conception that
considering the religion as an “human mistake” resulted from the absence of social practice and
science can lead to neutralism and immaterial.
The auther is based on the establishment of tolerantism in our republic which is very
essensial for democratic and legitmate state and emphisize that state agencies have registrated
more than 350 religion bodies and 30 of them are non islamic (protestant, provaslav, judish,
molokan) .The main goals of the Islam are to save the social justice, equlity of all the human
beings and to keep the islam religion out from unsensible ideas and changes.